2020
DOI: 10.3390/ma13173846
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Defects and Effects in Germanate and Tellurite Glasses

Abstract: This review focuses on the radiation-induced changes in germanate and tellurite glasses. These glasses have been of great interest due to their remarkable potential for photonics, in terms of extended transmission window in the mid-infrared, ability of rare-earth loading suitable with a laser, and amplification in the near- and mid-infrared or high nonlinear optical properties. Here, we summarize information about possible radiation-induced defects, mechanisms of their formation, and the influence of the glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 119 publications
(154 reference statements)
0
8
0
Order By: Relevance
“…At the same time, understanding the processes of interaction of ionizing radiation on semiconductor devices, as well as microelectronic devices, is very important for the design and development of electronic devices, and therefore, much attention has been paid to this area in recent years [ 8 , 9 , 10 ]. Note that while the processes of radiation damage are fairly well understood in binary oxides and halides [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], the situation in multicomponent glasses is still far from detailed [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, understanding the processes of interaction of ionizing radiation on semiconductor devices, as well as microelectronic devices, is very important for the design and development of electronic devices, and therefore, much attention has been paid to this area in recent years [ 8 , 9 , 10 ]. Note that while the processes of radiation damage are fairly well understood in binary oxides and halides [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], the situation in multicomponent glasses is still far from detailed [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several studies on oxide gallo-germanate glasses have been reported due to their potential use in photonics. The properties of this kind of glass have been explored in Ga 2 O 3 –GeO 2 –BaO [ 1 ], Ga 2 O 3 –GeO 2 –BaO–K 2 O [ 2 ], Ga 2 O 3 –GeO 2 –La 2 O 3 –BaO [ 3 , 4 ], and Ga 2 O 3 –GeO 2 –BaO–La 2 O 3 –Y 2 O 3 [ 5 ] systems, demonstrating that gallo-germanate glasses offer wide optical transparency (∼6 µm), low phonon energy (~850 cm −1 ), and a high linear and nonlinear refractive index [ 6 ]. Moreover, gallo-germanate glasses are mechanically resistant and chemically stable, which allows their use in the production of fibers and waveguides [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a very extensive literature on tellurite glasses doped with Er 3+ ions [ 17 ], Ho 3+ , and/or Tm 3+ ions [ 7 , 18 , 19 ]. Such glasses are suitable for IR (mid-IR) phosphors when excited with 800 nm radiation [ 1 , 9 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%